Review study on stabilized fly ash type c as admixture in sub-grade of pavement - Mahmood, Muhammad Amirul Hakim; A.Khalifa, Nasradeen (Penerbit UTHM, 2022)
Fly ash, also known as the residues of fine particles that formed with flue gases is a by-product which can be found at thermal power stations. There are two types of fly ash, which are Type C and Type F. This material can be used in construction of buildings or infrastructures as a new alternative to reduce material costs if the material can achieve an adequate performance as a construction material. With the use of fly ash, Portland cement usage can be reduced hence it promotes sustainable development. The aim of this study are to evaluate the engineering properties and adequacy of stabilized fly ash Type C as an admixture to stabilize subgrade soil. Several past researches are reviewed to study the chemical and physical properties of stabilized fly ash Type C and they conducted various tests such as unconfined compression test, California Bearing Ratio (CBR) test, and resilient modulus test on the soil specimens containing stabilized fly ash Type C material. It was found that fly ash Type C with almost optimum water content (less than 5%) significantly increase the compressive strength, CBR value and resilient modulus of stabilized soil when mixed. Therefore, these researches showed that fly ash-stabilized material (FASM) significantly improve bearing resistance and stiffness of sub-grade in a road pavement.